ER modelling – a zoom in and zoom out approach. (30th October 2009) - Wang, Xiong
Entity-relationship modelling is an effective design method for relational databases. It is covered in almost every textbook on database systems. Yet, there is not a single book that gives a systematic process on building an entity-relationship model step-by-step from the requirement specifications. In this paper, a zoom in and zoom out approach for such a process is introduced. A toolkit called ERZoom has been developed to assist the designer in the zoom in and zoom out design process. ERZoom provides a unique feature that enables the designer to view a selected subset of the entities and their attributes, while hiding the rest of the entity-relationship model. This is especially useful in distributed database design where vertical fragmentation is a major issue. ERZoom is developed as an open source package using Java. The zoom in and zoom out approach has been taught to beginners for several years and was well-received by the audience.